2009
DOI: 10.1097/ta.0b013e31818cae0c
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a New Trauma Center on an Existing Nearby Trauma Center

Abstract: The addition of a new trauma center in the Bronx had a negative impact on a near-by trauma center. Significant reductions in the volume of severely injured patients had a negative impact on factors not routinely measured like resident education, staff competency, and research. It is possible that these factors are at least partially responsible for the increased mortality rates seen after designation. These considerations are not routinely considered during the designation of new trauma centers and may actuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…19 Recent studies have demonstrated that patients treated at established centers may have survival advantages over those managed at newly created centers, 20 and a new trauma center may have potential negative impact on a nearby established one. 21 Taken together, it is unlikely that HK will benefit from designating more trauma centers. Indeed, an important question is whether service may be consolidated to concentrate clinical experience in fewer centers.…”
Section: Discussionmentioning
confidence: 98%
“…19 Recent studies have demonstrated that patients treated at established centers may have survival advantages over those managed at newly created centers, 20 and a new trauma center may have potential negative impact on a nearby established one. 21 Taken together, it is unlikely that HK will benefit from designating more trauma centers. Indeed, an important question is whether service may be consolidated to concentrate clinical experience in fewer centers.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have both supported 2–4, 26 and refuted 6, 7, 9 the premise that increased trauma center volume results in better outcomes. Our results showed a broad effect on survival in those with severe injuries.…”
Section: Discussionmentioning
confidence: 99%
“…We will develop a rigorous systematic search strategy with a health sciences librarian who has systematic review experience using published guidelines of The Cochrane Collaboration (see Additional file 2 for a preliminary version) [16]. The strategy will be developed for MEDLINE and EMBASE using keywords and MeSH (MEDLINE) or EMTREE (EMBASE).…”
Section: Methodsmentioning
confidence: 99%